2012
DOI: 10.1111/j.1478-3231.2012.02761.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoural hydroxyapatite nanoparticles‐mediated hepatoma‐targeted trans‐arterial embolization gene therapy: in vitro and in vivo studies

Abstract: In all, this new treatment based on nHAP can enhance therapeutic effect of HCC safely both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
(45 reference statements)
1
29
0
Order By: Relevance
“…11 Thus, our first aim was to enhance the effectiveness of LNT treatment through a cooperative gene effect and out second was to determine the possible molecular mechanism of this enhancement. The therapeutic protocol was designed using p53+Rb, with the aim of enhancing the antitumor effects obtained with p53 alone in the former LNT for VX2 tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Thus, our first aim was to enhance the effectiveness of LNT treatment through a cooperative gene effect and out second was to determine the possible molecular mechanism of this enhancement. The therapeutic protocol was designed using p53+Rb, with the aim of enhancing the antitumor effects obtained with p53 alone in the former LNT for VX2 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The event used as an endpoint was death. A P-value of #0.05 was considered For target gene expression, a previous study 11 identified the successful gene transduction only in tumor cells by observing the green fluorescence and immunostained band of EGFPp53 fusion protein using a fluorescent microscope and Western blot, respectively. This work also detected the specific expression of EGFP-p53 in nanoplex-p53/ Lipiodol (Group C) and nanoplex-(p53+Rb)/Lipiodol (Group E) group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al 21 reported that polypolex inhibited the growth of HepG2 cells and induced apoptosis, while keeping safe to L02 cell line at the same concentration. The authors deemed the different result of cytotoxicity was due to the different swollen ability between the tumor and normal cells.…”
Section: Cytotoxicity Of Au Ncs In Human Liver Cancer Cellsmentioning
confidence: 99%